IMPLEMENTATION OF PERIOPERATIVE PAIN MANAGEMENT FOR MR. A WITH APPENDICITIS AT UPT RSUD LABUANG BAJI MAKASSAR - Risnawati; Tutik Agustini; Nur Wahyuni Munir (PT. Jurnal Center Indonesia Publisher, 2026)
Appendicitis is an acute inflammatory condition of the appendix that requires prompt surgical intervention and comprehensive perioperative nursing care to prevent complications. This study aims to describe the application of perioperative pain management in a patient with appendicitis at UPT RSUD Labuang Baji Makassar. A descriptive case study design is employed using a perioperative nursing care approach covering preoperative, intraoperative, and postoperative phases. The subject is a 44-year-old male patient diagnosed with appendicitis who undergoes appendectomy. Data are collected through interviews, observation, physical examination, and documentation, with pain assessed using the Numeric Rating Scale. Nursing interventions focus on non-pharmacological pain management, including deep breathing relaxation in the preoperative phase and Benson relaxation therapy in the postoperative phase. The results show a decrease in pain intensity and anxiety before surgery, effective control of intraoperative bleeding, and gradual reduction of postoperative pain accompanied by improved tissue integrity and patient knowledge. This case study demonstrates that appropriate non-pharmacological nursing interventions effectively support perioperative pain management and enhance patient recovery in appendicitis cases.